2010
DOI: 10.1093/annonc/mdp499
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein induces MCF-7 breast cancer cell apoptosis via the mitochondrial pathway

Abstract: Accordingly, daidzein could induce breast cancer cell apoptosis through the mitochondrial caspase-dependent cell death pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(96 citation statements)
references
References 24 publications
9
86
1
Order By: Relevance
“…Recently, Jin et al (2010) trying to exploit phytoestrogen to induce apoptosis in MCF-7, they used Daidzein which belongs to the isoflavone family, which is the most commonly ingested and most intensely studied type of phytoestrogen, often found in nuts, fruits, soybeans, and soy-based products. In their studies Jin et al (2010) demonstrated that daidzein induces apoptosis through the generation of ROS that perturb mitochondrial function, leading to mitochondrial permeability, cytochrome c release, and caspase activation. They further reported the loss of the antiapoptotic mitochondrial Bcl-2 protein as partially responsible for the opening of the mitochondrial permeability transition pore.…”
Section: Small Molecules Targeting Intrinsic Pathway In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Jin et al (2010) trying to exploit phytoestrogen to induce apoptosis in MCF-7, they used Daidzein which belongs to the isoflavone family, which is the most commonly ingested and most intensely studied type of phytoestrogen, often found in nuts, fruits, soybeans, and soy-based products. In their studies Jin et al (2010) demonstrated that daidzein induces apoptosis through the generation of ROS that perturb mitochondrial function, leading to mitochondrial permeability, cytochrome c release, and caspase activation. They further reported the loss of the antiapoptotic mitochondrial Bcl-2 protein as partially responsible for the opening of the mitochondrial permeability transition pore.…”
Section: Small Molecules Targeting Intrinsic Pathway In Breast Cancermentioning
confidence: 99%
“…The loss of caspase-3 expression as well as defaults in cytochrome c release from the mitochondria, which is required in most apoptotic pathways to activate caspase-3 through caspase-9 activation, are associated with multidrug resistance. Accordingly, expression of caspase-3 in the human MCF-7 breast tumor cell line (which is deficient for caspase-3) restores the apoptotic response to the topoisomerase II inhibitor, etoposide [50]. Caspase-3 was also involved in breast cancer cell apoptosis upon exposure to anthracyclines and cisplatin [27,51].…”
Section: Caspase 3 In Breast Cancermentioning
confidence: 99%
“…Downregulation of Bcl-2 protein induces cell death though disruption of mitochondrial membrane permeability and subsequent release of cytochrome c (Kroemer et al, 2007). Several studies have reported disruption of mitochondrial membrane permeability in MCF-7 cells (Kallio et al, 2005;Jin et al, 2010). After the release of cytochrome c from the mitochondria, the apoptosome (which contain cytochrome c, Apaf-1, AIF, and procaspase-9)…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent probes such as DiOC 6 can be used to measure the mitochondrial transmembrane potential change. 45 Treatments of HeLa cells with epirubicin and/or hepcidin 2-3 for 24 h demonstrated significant declines in ΔΨ m ( Figure 5A). PEGylated liposomal epirubicin and hepcidin 2-3 further diminished ΔΨ m .…”
Section: Pegylated Liposomal Epirubicin and Hepcidin 2-3 Treatment Rementioning
confidence: 96%